Hypoxanthine-Guanine Phosphoribosyltransferase/adenylate Kinase From Zobellia galactanivorans: A Bifunctional Catalyst for the Synthesis of Nucleoside-5′-Mono-, Di- and Triphosphates (2020)
In our search for novel biocatalysts for the synthesis of nucleic acid derivatives, we found a good candidate in a putative dual-domain hypoxanthine-guanine phosphoribosyltransferase (HGPRT)/adenylate kinase (AMPK) from Zobellia galactanivorans (ZgHGPRT/AMPK). In this respect, we report for the first time the recombinant expression, production, and characterization of a bifunctional HGPRT/AMPK. Biochemical characterization of the recombinant protein indicates that the enzyme is a homodimer, with high activity in the pH range 6-7 and in a temperature interval from 30 to 80°C. Thermal denaturation experiments revealed that ZgHGPRT/AMPK exhibits an apparent unfolding temperature (Tm) of 45°C and a retained activity of around 80% when incubated at 40°C for 240 min. This bifunctional enzyme shows a dependence on divalent cations, with a remarkable preference for Mg2+ and Co2+ as cofactors. More interestingly, substrate specificity studies revealed ZgHGPRT/AMPK as a bifunctional enzyme, which acts as phosphoribosyltransferase or adenylate kinase depending upon the nature of the substrate. Finally, to assess the potential of ZgHGPRT/AMPK as biocatalyst for the synthesis of nucleoside-5′-mono, di- and triphosphates, the kinetic analysis of both activities (phosphoribosyltransferase and adenylate kinase) and the effect of water-miscible solvents on enzyme activity were studied.